Risk of obstetric anal sphincter injury in women having a vaginal birth after a previous caesarean section: A population-based cohort study. (May 2019) - Jardine, Jennifer E.; Knight, Hannah E.; Carroll, Fran E.; Gurol-Urganci, Ipek
Abstract: Objective: Caesarean section is increasing in prevalence and with it the proportion of women going into their next pregnancy with a scar on their uterus. For women considering vaginal birth after caesarean (VBAC), accurate information about the associated risks is required. Study design: The cohort comprised 192, 057 women who had a vaginal delivery of a singleton, term, cephalic infant between the 1st April 2013 and the 31st March 2014 in England: 182, 064 women who were having their first baby, and 9993 women who were having a second baby after a previous caesarean delivery. Their risk of an obstetric anal sphincter injury (OASI) was compared using a mixed-effects logistic regression model, adjusting for maternal age, use of instrument, episiotomy, prolonged labour, shoulder dystocia, and demographic factors. Results: The OASI rate was 5.0% in primiparous women, 5.8% in secondiparous women undergoing VBAC after previous elective caesarean, and 7.6% in secondiparous women undergoing VBAC after previous emergency caesarean. Women having a VBAC for their second baby following an emergency caesarean section in their first delivery had a higher rate of OASI than primiparous women (adjusted OR 1.31; 95% CI: 1.20, 1.43), For women with a previous elective delivery, the rates are similar to those for primiparous women. Conclusion: Women having a VBAC after emergency caesarean have a higher rate of OASI than primiparous women. This is important in the counselling of women considering VBAC.